Electrocardiographic Abnormalities in Canine Dilated Cardiomyopathy and their Management - K, Sesha Saikrishna; K, Jeyaraja; S, Vairamuthu; Md, Shafiuzama; P, Selvaraj (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Dilated cardiomyopathy (DCM) is one of the commonly acquired myocardial disease of dogs which most often is accompanied by electrocardiographic abnormalities. The present study was aimed to identify the electrocardiographic (ECG) abnormalities that were present in DCM affected dogs as well as their management. A total of 52 dogs with DCM were evaluated electrocardiographically using RMS Vesta 301i as per standard procedure. Pre-therapeutic electrocardiographic evaluation revealed normal sinus rhythm in 15 cases (28.84%), sinus tachycardia in 18 cases (34.61%), atrial fibrillation in 8 cases (15.38%), ST coving in 6 cases (11.53%), reduced ‘R’ amplitude in 5 cases (9.6%), junctional premature complexes in 2 cases (3.84%), ventricular premature complex in 2 (3.84%), atrial flutter in 1 case (1.92%) and isorhythmic atrioventricular disassociation in 1 case (1.92%). All the cases were treated for DCM using standard protocol. Atrial fibrillation and flutter were treated with Diltiazem @ 1-1.5 mg/kg three times a day and Digoxin @ 0.003 mg/kg twice a day orally and ventricular premature complex was treated with Sotalol @ 1-2 mg/kg two times a day orally. Six cases of atrial fibrillation was presented for follow-up and all achieved effective control of heart rate i.e., rate control and two of them reverted to normal sinus rhythm i.e., rhythm control, one to atrial flutter and three persisted with atrial fibrillation. VPC’s in both the dogs were successfully controlled by 15th day of therapy.
Keywords: Antiarrythmics; Arrhythmias; Atrial fibrillation; Dilated cardiomyopathy; Ventricular premature complex